Improving bacterial cellulose for blood vessel replacement: functionalization with a chimeric protein containing a cellulose-binding module and an adhesion peptide - Andrade, Fábia K. (2010)
Chimeric proteins containing a cellulose-binding module (CBM) and an adhesion peptide (RGD or GRGDY) were produced and used to improve the adhesion of human microvascular endothelial cells (HMEC) to bacterial cellulose (BC). The effect of these proteins on the HMEC–BC interaction was studied. The results obtained demonstrated that recombinant proteins containing adhesion sequences were able to significantly increase the attachment of HMEC to BC surfaces, especially the RGD sequence. The images obtained by scanning electron microscopy showed that the cells on the RGD-treated BC present a more elongated morphology 48 h after cell seeding. The results also showed that RGD decreased the in-growth of HMEC cells through the BC and stimulated the early formation of cord-like structures by these endothelial cells. Thus, the use of recombinant proteins containing a CBM domain, with high affinity and specificity for cellulose surfaces allows control of the interaction of this material with cells. CBM may be combined with virtually any biologically active protein for the modification of cellulose-based materials, for in vitro or in vivo applications.